(untitled) (Canadian Hematology Today, 2022)
Waldenström macroglobulinemia (WM) is an indolent B-cell non-Hodgkin lymphoma (NHL) characterized by malignant B cells that produce IgM monoclonal protein. Like other indolent B-cell NHLs, treatment is indicated when patients are symptomatic with lymphadenopathy, splenomegaly or have detrimental cytopenias, but uniquely hyperviscosity and other complications related to gammopathy may present a need for treatment. Currently in Canada chemoimmunotherapy using bendamustine and rituximab (BR) is the favored therapeutic combination for treatment-naïve patients with WM due to a superior efficacy and toxicity profile compared to rituximab plus CHOP and a fixed duration schedule. The availability of Bruton’s tyrosine kinase inhibitors (BTKi) have transformed the treatment landscape for patients with WM, particularly in the relapsed setting. Ibrutinib, a once-daily BTKi, was approved by Health Canada (HC) for WM in 2016 based on two non-randomized studies showing high response rates in heavily pretreated rituximab-refractory patients with sustained efficacy (86% progression-free survival (PFS) at 18 months) and acceptable tolerability. Ibrutinib forms an irreversible covalent bond to the cysteine residue (C481) at the active binding site of BTK. Patients with mutated MYD88 (MYD88MUT), who represent over 90% of patients with WM, have a higher rate of response with ibrutinib than those without (MYD88WT). Aside from its impressive efficacy, its oral administration offers a major advantage in terms of convenience for patients and lower administrative costs for publicly funded health care systems such as in Canada. The toxicity of ibrutinib has become of greater concern with the ongoing emergence of trial data and real-world clinical experience with the drug. The indefinite duration of treatment results in extended exposure of a primarily elderly patient population to toxicities such as increased bleeding risk, atrial fibrillation, hypertension, and infection. Discontinuation of ibrutinib due to adverse events occurs at a higher rate in the real-world compared to clinical trials and has been associated with an inferior overall survival in WM. Fortunately, several BTKis have recently emerged. Both acalabrutinib and zanubrutinib also bind irreversibly to BTK at C481, but both have more selectivity for targeting BTK than ibrutinib. Data has demonstrated that tighter and more selective binding of BTK does translate into fewer adverse effects for patients. The most informative study to date in this regard is the randomized phase 3 clinical trial comparing ibrutinib to zanubrutinib, the ASPEN study. ASPEN is the largest multicentre phase 3 trial to date randomizing 201 patients with MYD88MUT WM to receive ibrutinib at 420 mg daily (n=99) vs. zanubrutinib 160 mg twice daily (n=102), with 37 patients being treatment-naïve and 164 being relapsed or refractory (R/R) with a median of 1 prior line of therapy (range 1-8). The median age at enrolment was 70 however more patients randomized to zanubrutinib than to ibrutinib were >75 years old (33% vs 22%, respectively). Although not statistically significant, a higher rate of complete response (CR)/very good partial response (VGPR) was observed for zanubrutinib vs ibrutinib (28% vs 19%, respectively). With a median follow up of 19.4 months the major response rates (77% vs. 78%) and PFS (85% vs. 84% at 18 months) were also not statistically different in patients receiving zanubrutinib vs. ibrutinib, respectively. However, zanubrutinib was associated with a trend towards less toxicity. In particular, the incidences of all grade atrial fibrillation, diarrhea, bruising, muscle spasms, peripheral edema, and pneumonia were over 10% higher among ibrutinib-treated patients. The incidence of neutropenia was higher for zanubrutinib-treated patients (> 10% difference), although grade ≥3 infection rates were similar in both arms (1.2 and 1.1 events per 100 person-months). Further, more ibrutinib-treated patients required dose reductions (23% vs. 14%) and discontinued treatment (9% vs. 4%) due to adverse events. An analysis of quality of life (QoL) instruments demonstrated a trend towards greater improvement in the zanubrutinib arm, particularly in the subgroup of patients who achieved VGPR. These QoL improvements were most notable in validated instrument subscales encompassing appetite, dyspnea, fatigue, physical functioning and role functioning. The ASPEN trial formed the basis for recent approval of zanubrutinib for WM by HC. Although provincial funding is not yet in place, clinicians in Quebec can access zanubrutinib through the Patient d’exception mechanism. As Canadian hematologists will be able to choose a BTKi for their patient with R/R WM, it is important to review the toxicities reported in trials. Toxicities of BTKis and their management will be discussed in this article.